2020
DOI: 10.3390/pharmaceutics12030251
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotechnical Development of a Nasal Drug Delivery Composite Nanosystem Intended for Alzheimer’s Disease Treatment

Abstract: Direct nose-to-brain delivery has been raised as a non-invasive powerful strategy to deliver drugs to the brain bypassing the blood-brain barrier (BBB). This study aimed at preparing and characterizing an innovative composite formulation, associating the liposome and hydrogel approaches, suitable for intranasal administration. Thermosensitive gel formulations were obtained based on a mixture of two hydrophilic polymers (Poloxamer 407, P407 and Poloxamer 188, P188) for a controlled delivery through nasal route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Moreover, a decrease in the formulations' apparent viscosity with time was not observed, which indicates the absence of thixotropy (the upper and lower curves of the rheograms overlap). Other authors have reported the same behavior as desirable for nasal formulations [18][19][20]. Figure 1B also shows the effect of lipid-based nanosystems on the flow behavior.…”
Section: Rheological and Texture Analysissupporting
confidence: 66%
“…Moreover, a decrease in the formulations' apparent viscosity with time was not observed, which indicates the absence of thixotropy (the upper and lower curves of the rheograms overlap). Other authors have reported the same behavior as desirable for nasal formulations [18][19][20]. Figure 1B also shows the effect of lipid-based nanosystems on the flow behavior.…”
Section: Rheological and Texture Analysissupporting
confidence: 66%
“…This hydrogel is also able to encapsulate curcumin and release it slowly, and although this hydrogel has not been tested yet in vivo, it could represent a promising therapeutic strategy [ 184 ]. Recently, a combinatory approach has also been tested, combining liposomes with hydrogels and delivering an active pharmaceutical ingredient, in order to improve bioavailability [ 185 ].…”
Section: The Role Of Scaffolds In Developing Regenerative Therapiementioning
confidence: 99%
“…pH values of NEs were measured between 3.25 and 3.56, which are in the acceptable range for nasal preparation (6 ± 3 ) [50].…”
Section: Physicochemical Characterization Of Nes Containingmentioning
confidence: 92%